CO-CREATION OF LEARNING AS AN ENGAGING PRACTICE - Kaminskiene, Lina; Khetsuriani, Nano (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper focuses on the co-creation of learning as a contemporary approach to engage learners. Today researchers discuss different engaging practices based on the learner-centred strategies, trying to respond to variety of personal learning needs, requirements and interests. By having a central role in the process, learners can decide how to organize their learning based on their abilities and stay actively engaged in the process. The idea of learners as change agents, active partners, producers and co-creators of their own learning has been a topic of increased interest in recent years. Development of student-led, collaborative initiatives leads educational institutions towards promoting co-creating of learning processes and co-created learning outputs.